The examined life : readings from Western philosophy from Plato to Kant - Rosen, Stanley, 1929-2014. (New York : Random House, 2000)
Over 35 excerpts from philosophers from Aristotle to Hume, arranged by discipline: social and political philosophy, philosophy of religion, philosophy of art and aesthetics, metaphysics, epistemology, and philosophy of science.
pt. 1. Social and political philosophy. Selections from: Symposium / Plato -- Gorgias / Plato -- Republic / Plato -- Politics / Aristotle -- The prince / Niccolo Machiavelli -- Leviathan / Thomas Hobbes -- The first and second discourses / Jean-Jacques Rousseau -- pt. 2. Philosophy of religion. Selections from: Confessions / Augustine -- Guide for the perplexed / Maimonides -- Pensees / Blaise Pascal -- Lectures on the philosophy of religion / Georg Wilhelm Friedrich Hegel -- Fear and trembling / Soren Kierkegaard -- pt. 3. Philosophy of art and culture. Selections from: Republic / Plato -- Poetics / Aristotle -- On the aesthetic education of man in a series of letters / Friedrich Schiller -- The birth of tragedy / Friedrich Nietzsche -- Art as experience / John Dewey -- Aesthetic theory / Theodor Adorno -- pt. 4. Metaphysics. Selections from: Metaphysics / Aristotle -- Meditations / Rene Descartes -- Lectures on the history of philosophy / Georg Wilhelm Friedrich Hegel -- Reflections on the common concept of justice / Gottfried William Leibnitz -- Prolegomena to any future metaphysics / Immanuel Kant -- The blue and brown books / Ludwig Wittgenstein -- pt. 5. Epistemology. Selections from: Meno / Plato -- Posterior analytics / Aristotle -- Meditations / Rene Descartes -- Abstract on a Treatise of Human Nature / David Hume -- "Questioning as a philosophical method" / Jaakko Hintikka -- pt. 6. Philosophy of scienc Selections from: Against method / Paul Feyerabend -- The structure of scientific revolutions / Thomas Kuhn -- The crisis of European sciences / Edmund Husserl -- "The concept of biological progress" / Francisco J. Ayala -- Science and the scientist / Henri Poincare -- Science and the hypothesis / Henri Poincare -- "Logic and mathematics"
Includes bibliographical references (p. 611-614) and index.
Keywords: Philosophy; Geschichte 400 v. Chr.-1800.